2006
DOI: 10.1097/01.bto.0000252114.20634.ce
|View full text |Cite
|
Sign up to set email alerts
|

Elbow Biomechanics During Sports: 21st Century Research

Abstract: Injuries to the elbow joint are becoming more and more prominent in today's sporting society. This is largely because of the biomechanical demands during popular sports such as baseball, softball, and tennis; wherein the majority of elbow injuries occur. Implications for injuries in these sports range from overuse to incorrect mechanics, which cause increased loads at the elbow joint. This can be seen in the overhead throwing motion where a large varus torque leads to tensile injuries in the medial elbow and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…8 However, cadaveric research has shown that the UCL can provide only about 32 N·m of elbow varus torque. 8,12 Although both biomechanical modeling and cadaveric research have limitations and inaccuracies, these studies support the explanation that peak tension in the UCL is dangerously high when the pitcher’s arm is externally rotated, and repetitive pitching can create tears in the anterior bundle of the UCL.…”
mentioning
confidence: 72%
“…8 However, cadaveric research has shown that the UCL can provide only about 32 N·m of elbow varus torque. 8,12 Although both biomechanical modeling and cadaveric research have limitations and inaccuracies, these studies support the explanation that peak tension in the UCL is dangerously high when the pitcher’s arm is externally rotated, and repetitive pitching can create tears in the anterior bundle of the UCL.…”
mentioning
confidence: 72%
“…Typically, the pitching motion is divided into the following 6 phases: windup, stride, arm cocking, arm acceleration, arm deceleration, and follow-through (Figures 1 and 2 and Supplementary Videos 1 and 2). 11,14,15,17,18,19,22,23,24,25,32,34,51,52,54 The windup phase commences when the pitcher begins lifting the lead leg while the hands are held together high at the chest. The windup phase ends when the lead knee has reached its maximum height.…”
Section: Windup Phasementioning
confidence: 99%
“…An additional significant risk factor for increased elbow and shoulder stress is poor pitching mechanics. 1,6,24,25,49,51,53 In the 20th century, throwing mechanics were usually evaluated via the naked-eye or standard 2-dimensional video. Automated tracking technology has changed the way throwing mechanics are analyzed, providing accurate and reliable 3-dimensional (3D) kinematic (motions) and kinetic (forces and torques) measurements.…”
mentioning
confidence: 99%